Leaf photosynthetic characteristics of Corylus heterophylla and hybrid hazel (Corylus heterophylla × Corylus avellana) - LIU Jian-feng; CHENG Yun-qing; LIU Qiang; WANG Zhan-wu; YAN Kun (浙江大学学报. 农业与生命科学版)
LI-6400 /XT photosynthesis system was used to measure leaf photosynthetic characteristics of two Corylus heterophylla germplasms (PZ1 and PZ2) and three Corylus heterophylla × Corylus avellana hybrid hazelnut cultivars (PDH, DW and YZ). The results showed that light saturation points of five hazelnut germplasms were from 680 to 930 μmol·m-2·s-1, and their light compensation points were less than 50 μmol·m-2·s-1. Their maximum net photosynthetic rates were from 8 to 17 μmol·m-2·s-1, and their apparent quantum efficiencies were from 0.03 to 0.04. There were two peaks in photosynthesis changing curves of five hazelnut germplasms, and the peak values occurred at 8:00 and 17:00 o'clock, indicating that it was suitable for hazelnut to culture in weak illumination environment. There were differences in photosynthetic capability for the five hazelnut germplasms with the order as follows: PDH > DW > PZ1 > YZ > PZ2. CO2 compensation point, CO2 saturation points, maximum RuBP regeneration rates and carboxylation efficiency of five hazelnut germplasms were from 45 to 70 μmol·m-2·s-1, 880 to 1 350 μmol·m-2·s-1, 13 to 34 μmol·m-2·s-1 and from 0.03 to 0.05, respectively. The results above provide scientific base for hazelnut culture in Northeast China region.